Help Or Hindrance ? : The Impact of Harmonized Standards On African Exports - Czubala, Witold (The World Bank, 2007)
The authors test the hypothesis that product standards harmonized to de facto international standards are less trade restrictive than ones that are not. To do this, the authors construct a new database of European Union (EU) product standards. The authors identify standards that are aligned with ISO standards (as a proxy for de facto international norms). The authors use a sample-selection gravity model to examine the impact of EU standards on African textiles and clothing exports, a sector of particular development interest. The authors find robust evidence that non-harmonized standards reduce African exports of these products. EU standards which are harmonized to ISO standards are less trade restricting. Our results suggest that efforts to promote African exports of manufactures may need to be complemented by measures to reduce the cost impacts of product standards, including international harmonization. In addition, efforts to harmonize national standards with international norms, including through the World Trade Organization Technical Barriers to Trade Agreement, promise concrete benefits through trade expansion